EDUKASI DAGUSIBU (DAPATKAN, GUNAKAN, SIMPAN DAN BUANG) OBAT DENGAN BENAR PADA PASIEN RAWAT JALAN RUMAH SAKIT PKU MUHAMMADIYAH WONOSOBO - Sidiq Himawan, Noor Syam; Wicaksono, Anggoro; Herawati, Lestari Wahyu (Transpublika Publisher, 2023)
Health problems arising from the use of drugs, such as lack of knowledge, misuse, side effects, and circulation of counterfeit drugs, are the focus of public attention. In this context, this study is seen as an effort to improve the understanding of the community, especially the patients of PKU Muhammadiyah Wonosobo Hospital, regarding drug management through the implementation of the DAGUSIBU program. The research method applied was pre-test post-test group design, where the DAGUSIBU counseling session was conducted on December 13, 2023, attended by 127 outpatients. The success of this activity was reflected in the high level of interest and enthusiasm of the participants towards the DAGUSIBU material, which included basic principles such as how to obtain, use, store, and dispose of medicines properly. The counseling process involved a series of activities, including a pre-test to assess participants' initial understanding, delivery of the DAGUSIBU materials, and a post-test to measure knowledge improvement. Data analysis showed a significant increase in participants' understanding, with a mean pre-test score of 36 increasing to 74 in the post-test. Statistical tests with paired t-test verified a significance of p=0.000 (p<0.05), confirming that the DAGUSIBU educational approach was successful in significantly improving respondents' knowledge. Thus, it can be concluded that the DAGUSIBU counseling at PKU Muhammadiyah Wonosobo Hospital was not only effective in improving participants' understanding of how to obtain, use, store, and dispose of medication, but also created a significant positive impact on overall medication management.